Suscetibilidade de Anticarsia gemataiis a inseticidas a base de Bacillus thuringiensis e histopatologia do intestino medio de linhagens resistentes e suscetiveis a Cry1Ac - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The production of extensive crops such as soybean and corn in Brazil faces serious problems that affect their productivity, such as pest insect damage. Among them, the most important defoliators are Anticarsia gemmatalis. Studies related to the susceptibility of these insects to commercial products with different Cry toxin composition are desirable to avoid cross resistance between Bt crops and commercial Bt products. The objectives of this work were to determine the susceptibility of resistant and susceptible A. gemmatalis to Cry1Ac toxin. Um addition, our purpose was to quantify cellular response of the midgut of A. gemmatalis inoculated with HD-73 bacterium. Populations from both insects were exposed to the commercial products Agree®, Dipel® and Xentari®, which contain a complex of Bt toxins. Mortality assessment was performed by day 7th and data analysis was performed using the Weibull-2 model. Cells were quantified in midgut of A. gemmatalis treated with: susceptible strain infected with Bt, susceptible strain without inoculation, resistant strain infected with Bt and resistant strain without inoculation. Digital images captured from slides were used to quantify different types of intestinal cells. Data were submitted to ANOVA analysis Tukey= 5%. The biological product that showed the highest activity, both in the resistant and susceptible strains of A. gemmatalis, was Xentari® and the product with the lowest biological activity was Dipel®, and Dipel® showed 42-fold lower activity in the resistant strain; resistant rates for Agree® and Xentari® were approximately 18 and 11-fold. In this study, we observed significant differences in numbers of each type of midgut cell between treatments and also between the anterior and hind regions of the midgut, which shows differential response between susceptible and resistant strains.
Keywords: lagarta-da-soja; intestino médio; bactérias entomopatogênicas; Bacillus thuringiensis kurstaki; Bacillus thuringiensis aizawai; velvetbean caterpillar; midgut; entomopathogenic bacteria; Bacillus thuringiensis kurstaki; Bacillus thuringiensis aizawai; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA